Kontroversi Nilai Keadilan Sahabat dalam Studi Hadis - Ridwan, Ridwan (Al-Manahij: Jurnal Kajian Hukum Islam, 2007)
The position of companions in ‘ulum al-hadith mainly related to their justice value has brought out controversy. Rasulullah stated in his speech ‘the best generation is mine and the next’. It legitimates the theology about companions’ position in religious frame. Minimally there are three different mainstreams Mu’tazilah (ideoligical group), Abi al-Sunnah majority (idealist group) Ahl-al Sunnah miniroty (realism group) in judjing the justice value of prophet’s companions. The root of the problem Interpreting Al-Qur’an and hadis as well as humanity and sacred value.